2018
DOI: 10.24095/hpcdp.38.6.03f
|View full text |Cite
|
Sign up to set email alerts
|

Tendances canadiennes en matière de mortalité liée aux opioïdes et d’invalidité découlant d’un trouble de consommation d’opioïdes, à la lumière de l’Étude sur la charge mondiale de morbidité (1990-2014)

Abstract: Introduction Plusieurs régions du Canada ont récemment connu de brusques hausses de surdoses d’opioïdes ainsi que des hospitalisations et des décès connexes. Cet article traite de la mortalité liée aux opioïdes et de l'invalidité découlant d'un trouble de consommation d’opioïdes au Canada entre 1990 et 2014, à la lumière des données de l’Étude sur la charge mondiale de morbidité (ÉCMM). Méthodologie Nous avons utilisé les données de l’ÉCMM pour décrire l'évolution (19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…4 With the ongoing opioid crisis, there is an urgent need for effective nationwide actions to improve access to opioid agonist therapy (OAT). 5 OAT is recommended in Canada for the management of OUD related to prescription-type opioids (e.g., unregulated or prescription fentanyl). Opioid agonists such as methadone and buprenorphine exert their effect by binding to opioid receptors as complete and partial µ receptor agonists.…”
Section: Introductionmentioning
confidence: 99%
“…4 With the ongoing opioid crisis, there is an urgent need for effective nationwide actions to improve access to opioid agonist therapy (OAT). 5 OAT is recommended in Canada for the management of OUD related to prescription-type opioids (e.g., unregulated or prescription fentanyl). Opioid agonists such as methadone and buprenorphine exert their effect by binding to opioid receptors as complete and partial µ receptor agonists.…”
Section: Introductionmentioning
confidence: 99%
“…1 The age-standardized years-of-life lost from 1990 to 2014 due to opioid-related deaths have increased by 142.2%. 2 The negative impact of this crisis has extended to pregnant women and their offspring, as is evidenced by ongoing increases in rates of neonatal abstinence syndrome (NAS). Dawson et al reported a sixfold increase in NAS incidence in Ontario from 0.99 per 1,000 live births in 2003 to 5.94 in 2016.…”
mentioning
confidence: 99%